Reconstruction of the Judicial Commission’s Authority in Promoting Judges with Integrity - Widayati, Widayati; Winanto, Winanto; Haji Mohiddin, Mas Nooraini binti; Suwondo, Denny; Arpangi, Arpangi; Nur Hidayat, Yudhi Taufiq (Jurnal Hukum, 2023)
The authority of the Judicial Commission (KY) to supervise judges is diminishing due to opposition from the Supreme Court judges and constitutional judges. Cases of corruption and bribery involving Supreme Court judges and constitutional judges indicate that external oversight by the KY is crucial to maintaining judges' honor, dignity, and behavior. This research discusses the importance of external supervision in realizing the integrity of judges. The research uses a normative juridical approach, which examines norms or legal rules as a structure of norm systems related to a legal event. The data used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Based on the analysis, it is concluded that: 1) Supervision of judges, both internally and externally, is necessary and crucial to prevent them from abusing the freedom or independence given to them. Various cases of bribery and corruption involving judges indicate that without external supervision, there will be a risk of abuse of power. 2) KY, as an external supervisor, also needs to be given authority to select not only Supreme Court judges but judges at all levels of the judiciary within the Supreme Court. 3) KY conducts external monitoring of all judges, including judges to the Supreme Court and constitutional judges, to ensure the integrity of the judiciary. In order to ensure the optimal operation of KY's authority, KY representatives need to be established in provinces and districts/cities since judges are distributed throughout Indonesia both in provinces and districts/cities.